Acceptability Test and Nutritional Analysis of Tempeh and Moringa Leaf Soft Rice as Complementary Foods (MP-ASI) - Nadira Citra Pertiwi; Kurnia Mar’atus Solichah; Diah Puspitasari (International Journal of Public Health Excellence (IJPHE), 2026)
The age of 6–24 months is a crucial period for a child's growth and development, requiring optimal nutritional intake through the provision of Complementary Foods (MP-ASI). MP-ASI serves to supplement nutritional needs that can no longer be met by breast milk alone. Tempeh, as a source of plant-based protein, and moringa leaves, which are rich in iron and vitamins, have the potential to be developed into "nasi tim" (soft rice) as recommended by WHO. This study aims to assess the acceptability and analyze the nutritional content of tempeh and moringa leaf soft rice as a complementary food. The study used a non-factorial Completely Randomized Design (CRD) with three formulations: F1 (10% tempeh: 15% moringa leaves), F2 (20%: 10%), and F3 (30%: 15%). The acceptability test was conducted on 30 semi-trained panelists using a hedonic test for taste, color, aroma, and texture attributes, which were then analyzed using the Kruskal–Wallis test. The results showed significant differences in taste (p=0.00) and aroma (p=0.01), while color (p=0.08) and texture (p=0.01) did not differ significantly. Formulation F3 had the highest acceptability level, containing 75.38 kcal/100 g of energy, 3.55% protein, 15.36% carbohydrates, 0.12% fat, 1.46% crude fiber, and 0.92 mg/100 g of iron.